Impact of Front-line Demonstration in Transfer of Groundnut Production Technologies for the Livelihood Improvement of Oilseed Farmers - Madhushekar, B. Raja; Narendar, G.; Goverdhan, M.; Kumar, K. Avil (International Journal of Bio-resource and Stress Management, 2022)
The present investigation was conducted in different villages under DAATTC in Nalgonda & Yadadri Bhuvanagiri districts, Telangana state, India rabi season (October–January) during 2018–19 to 2020–21. Total 30 demonstrations were laid out on farmers’ fields in the district. The main objective of front-line demonstrations (FLDs) was to demonstrate the integrated nutrient management practices in groundnut for getting higher yields over farmer’s practice. The study was undertaken to evaluate the impact of frontline demonstrations on integrated nutrient management in Groundnut and in enhancing the income of oilseed farmers. The results of the study revealed that 80.00% of the respondents had less than 5a of land holding for cultivation of various crops, the average highest yield recorded was 2659 kg ha-1 in demonstration plot, a 12.53% increase over farmer’s practice (2362 kg ha-1). The extension gap ranged from 216–371 kg ha-1 and technology gap ranged between 998–1169 kg ha-1 respectively with average technology index of 29.09% during the demonstration years. Besides this, the demonstrated plots gave higher gross returns, net return with higher benefit cost ratio when compared to farmer’s practice. In present study efforts were also made to study the impact of FLD on horizontal spread which has increased by 242.85%, adoption levels by 136.75%. The study also revealed that there was significant increase in knowledge level of the farmers due to frontline demonstrations, a significant and positive relationship existed between farm size, extension contacts and yield.